Emergent laparoscopic dome resection and omental suturing to the splenic parenchymal edge for a spontaneously ruptured non-parasitic large splenic cyst in a pediatric patient: a case report - Kumiko Shono; Yoshiko Hashimoto; Takeshi Shono (Surgical Case Reports)
Abstract Background Spontaneously ruptured large splenic cyst is a rare in children, and traditionally total or partial splenectomy has been performed for treating an emergent case. We herein present a first case with spontaneously ruptured pediatric splenic cyst treated with emergent laparoscopic dome resection with omental suturing to the parenchymal edge of the spleen. Case presentation A 12-year-old girl with a spontaneously ruptured large non-parasitic splenic cyst (SC) was successfully treated by emergent laparoscopic dome resection with omental suturing to the edge of the splenic parenchyma. The patient presented with acute abdominal pain and was diagnosed with a ruptured non-parasitic SC and peritonitis by contrast-enhanced computed tomography (CT). Emergent laparoscopic dome resection of the SC and omental suturing to the splenic parenchymal edge were then performed. The protruding part of the cyst wall was completely resected using an ultrasonically activated device (USAD), and the greater omentum was then sutured to the anterior edge of the splenic parenchyma under a laparoscopic view. No complications were observed during the operation. A histological examination revealed a congenital splenic cyst lined by epithelial cells. The postoperative course was uneventful, and an ultrasound scan showed no evidence of cyst recurrence at 3 years after the operation. Conclusions This minimally invasive laparoscopic procedure was feasible and effective for treating a ruptured large splenic cyst in an emergent pediatric patient.